In search of Karl Polanyi's International Relations theory - Dale, Gareth (Review of International Studies, 2016)
Karl Polanyi is principally known as an economic historian and a theorist of international political economy. His theses are commonly encountered in debates concerning globalisation, regionalism, regulation and deregulation, and neoliberalism. But the standard depiction of his ideas is based upon a highly restricted corpus of his work: essentially, his published writings, in English, from the 1940s and 1950s. Drawing upon a broader range of Polanyi's work in Hungarian, German, and English, this article examines his less well-known analyses of international politics and world order. It sketches the main lineaments of Polanyi's international thought from the 1910s until the mid-1940s, charting his evolution from Wilsonian liberal, via debates within British pacifism, towards a position close to E. H. Carr's realism. It reconstructs the dialectic of universalism and regionalism in Polanyi's prospectus for postwar international order, with a focus upon his theory of 'tame empires' and its extension by neo-Polanyian theorists of the 'new regionalism and European integration. It explores the tensions and contradictions in Polanyi's analysis, and, finally, it hypothesises that the failure of his postwar predictions provides a clue as to why his research on international relations dried up in the 1950s.
Political Science
Keywords: CARR; Edward Hallett; 1892-1982; deregulation; international relations; liberalism; neoliberalism

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Political Science
Keywords: political theory; social theory

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Political Science
Keywords: history - modern; political history; political philosophy; political theory

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
History
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology